Pseudorapidity distribution of charged hadrons in proton-proton collisions at root s=13TeV - Khachatryan, V. (2015)
The pseudorapidity distribution of charged hadrons in pp collisions at root s = 13 TeV is measured using a data sample obtained with the CMS detector, operated at zero magnetic field, at the CERN LHC. The yield of primary charged long-lived hadrons produced in inelastic pp collisions is determined in the central region of the CMS pixel detector (vertical bar eta vertical bar < 2) using both hit pairs and reconstructed tracks. For central pseudorapidities (vertical bar eta vertical bar < 0.5), the charged-hadron multiplicity density is dN(ch)/d eta vertical bar(vertical bar eta vertical bar) < 0.5= 5.49 +/- 0.01 (stat) +/- 0.17 (syst), a value obtained by combining the two methods. The result is compared to predictions from Monte Carlo event generators and to similar measurements made at lower collision energies. (C) 2015 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V.